Paul Feyerabend Against Demarcation - Grigoryan, Kristine (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
Paul Feyerabend’s antidemarcationism is justified in the article. Feyerabend, analyzing the problem of demarcation, argues that there are no universal scientific criteria, and the problem of demarcation is a pseudoproblem. According to Feyerabend, actually there is no objective difference between the scientific and non-scientific knowledge. Moreover, he claims that we have no right to separate science from non-science.
Keywords: the problem of demarcation, antidemarcationism, scientific knowledge, nonscientific knowledge, scientific method, the principle of incommensurability, Paul Feyerabend